2007
DOI: 10.1007/s00122-007-0515-3
|View full text |Cite
|
Sign up to set email alerts
|

Joint modeling of additive and non-additive (genetic line) effects in multi-environment trials

Abstract: A statistical approach for the analysis of multi-environment trials (METs) is presented, in which selection of best performing lines, best parents, and best combination of parents can be determined. The genetic effect of a line is partitioned into additive, dominance and residual non-additive effects. The dominance effects are estimated through the incorporation of the dominance relationship matrix, which is presented under varying levels of inbreeding. A computationally efficient way of fitting dominance effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 40 publications
1
102
0
Order By: Relevance
“…populations with known pedigrees (Oakey et al 2007), but marker-based estimation of epistatic effects for natural populations appears possible only with more advanced statistical methodology, for example semiparametric mixed models and reproducing kernel Hilbert spaces (Gianola and Van Kaam 2008;Howard et al 2014). Another direction for future research is the estimation of heritability in the presence of additional random effects, which would increase the applicability to agricultural field trials (where the raw data are usually at plot rather than individual plant level).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…populations with known pedigrees (Oakey et al 2007), but marker-based estimation of epistatic effects for natural populations appears possible only with more advanced statistical methodology, for example semiparametric mixed models and reproducing kernel Hilbert spaces (Gianola and Van Kaam 2008;Howard et al 2014). Another direction for future research is the estimation of heritability in the presence of additional random effects, which would increase the applicability to agricultural field trials (where the raw data are usually at plot rather than individual plant level).…”
Section: Discussionmentioning
confidence: 99%
“…Differences between such blocks are usually best modeled using random block effects. The definition of heritability in such contexts is, however, far from obvious: Oakey et al (2007) proposed generalized heritability, but for natural populations this definition is not equivalent to the classical definition of heritability (Oakey et al 2007, p. 813). In this case the ratio of the estimated genetic variance over the total phenotypic variance could be used as a lower bound on heritability.…”
mentioning
confidence: 99%
“…The variance component associated with the additive genomic relationship matrix estimates additive polygenic genetic variance. The variance component associated with the identically and independently distributed line effects captures any other genotypic variance, which could include nonadditive variance (although dominance variance should be generally very low among highly homozygous lines) and also nonpolygenic variance due to individual genes with large effects (Oakey et al 2006(Oakey et al , 2007.…”
Section: Phenotypic Data Analysismentioning
confidence: 99%
“…The variance component associated with the additive genomic relationship matrix estimates additive polygenic genetic variance. The variance component associated with the identically and independently distributed line effects captures any other genotypic variance, which could include nonadditive variance (although dominance variance should be generally very low among highly homozygous lines) and also nonpolygenic variance due to individual genes with large effects (Oakey et al 2006(Oakey et al , 2007.For the purpose of estimating heritability of line mean values, both data sets were also analyzed using the modelwhere Y is the vector of BLUE values of each phenotype, u is a vector of inbred line additive effects, Z is a design matrix, and e is a vector of random residuals. The variance-covariance matrix of u is Var(u) = Gs 2 A ; where s 2 A is the additive genetic variance in the noninbred reference population and G is the realized additive relationship matrix based on all markers.…”
mentioning
confidence: 99%
“…More factors allow for greater flexibility, but may reduce model parsimony. Multiple researchers have demonstrated that a factor analytic structure can be combined with pedigree information to improve model fit, as measured by information criteria (Crossa et al, 2006;Oakey et al, 2007;Kelly et al, 2009;Beeck et al, 2010). These researchers have analyzed a limited number of real MET data sets; a simulation study could determine if the FA model with a GRM is the most effective model for a much wider range of MET.…”
Section: Introductionmentioning
confidence: 99%